Parasites as indicators of movement and population connectivity of a non-diadromous, tropical estuarine teleost: King threadfin Polydactylus macrochir - Moore, B.; Welch, D.; Newman, Stephen; Lester, R. (Wiley-Blackwell Publishing Ltd., 2012)
Temporal and spatial patterns in parasite assemblages were examined to evaluate the degree of movement and connectivity of post-recruitment life-history stages of a large, non-diadromous tropical estuarine teleost, king threadfin Polydactylus macrochir, collected from 18 locations across northern Australia. Ten parasites types (juvenile stages of two nematodes and seven cestodes, and adults of an acanthocephalan) were deemed to be suitable for use as biological tags, in that they were considered to have a long residence time in the fish, were relatively easy to find and were morphologically very different to each other which aided discrimination. Univariate and discriminant function analysis of these parasites revealed little difference in temporal replicates collected from five locations, suggesting that the parasite communities were stable over the timeframes explored. Univariate, discriminant function, and Bray-Curtis similarity analyses indicated significant spatial heterogeneity, with Bray-Curtis classification accuracies ranging from 55 to 100% for locations in north-western and northern Australia, 24 to 88% in the Gulf of Carpentaria, and 39 to 88% on the east coast of Queensland. Few differences were observed among locations separated by <200 km. The observed patterns of parasite infection are in agreement with concurrent studies of movement and connectivity of P. macrochir in that they indicate a complex population structure across northern Australia. These results should be considered when reviewing the management arrangements for this species. © 2012 The Authors. Journal of Fish Biology © 2012 The Fisheries Society of the British Isles.